An Open and Adaptable Platform for the elderly people and persons with disability to access the Information Society. The Naviga project - Gachet Paez, Diego; de Buenaga, Manuel; Villalba, M; Lara, Pedro (2010 4th International Conference on Pervasive Computing Technologies for Healthcare, 2010)
NAVIGA is an European project whose main goal is to design and develop a technological platform allowing elderly people and persons with disability to access the Internet and the Information Society through an innovative and adaptable navigator. NAVIGA also allows the creation of services targeted to social networks, mind training and personalized health care.